Northern Hemisphere ice sheet and ocean interactions during the last glacial period in a coupled ice sheet–climate model - L. Abot; A. Quiquet; C. Waelbroeck (Climate of the Past)
This study examines the interactions between the Northern Hemisphere ice sheets and the ocean during the last glacial period. Using the iLOVECLIM climate model of intermediate complexity and the GRISLI ice sheet model, we explore the consequences of an amplification of the melt rates beneath ice shelves on ice sheet dynamics and the associated feedbacks. First, the amplification of oceanic basal melt rates leads to significant freshwater release from both increased calving and basal melt fluxes. Grounding line retreat and dynamic thinning occur over the Eurasian and Iceland ice sheets, while the oceanic perturbation fails to trigger a grounding line migration over the coasts of Greenland and the eastern part of the Laurentide ice sheet. Second, similar to hosing experiments with no coupling between the climate and the ice sheets, the influx of fresh water temporarily increases sea-ice extent; reduces convection in the Labrador Sea; weakens the Atlantic meridional overturning circulation; lowers surface temperatures in the Northern Hemisphere, especially over the North Atlantic Ocean; and increases the subsurface temperatures in the Nordic Seas. Third, the freshwater release and latent heat effect on ocean temperatures lead to a decrease in ice sheet discharge (negative feedback) for the Greenland and Eurasian ice sheets. The Laurentide ice sheet does not feature significant volume variations in the experiments. On the one hand, the amplification of the shelf melt rates produces a weak perturbation due to low background temperatures and salinity at shelf drafts in Baffin Bay and the Labrador Sea according to the model. On the other hand, the Laurentide ice sheet in the fully coupled model may be overly stable. We show that we are able to force a grounding line retreat and a North American ice sheet volume decrease by imposing ad hoc constant oceanic melt rates. However, in both sets of perturbation experiments, the Hudson Strait ice stream does not exhibit the past dynamic instability indicated by the presence of Laurentide-origin ice-rafted debris in the North Atlantic sediment records. This suggests the possibility that the model is too stable, specifically in the Hudson Bay region. Different ice sheet geometries or modeling choices regarding the basal dynamics beneath the ice sheet could help address this issue. In summary, this study found that an episode of subsurface warming may trigger dynamical instabilities and ice discharges along the coasts of the Nordic Seas but subsequent ocean–ice sheet interactions may be characterized by negative feedback thus dampening ice discharges. This study also emphasizes the need for further research using fully coupled models to explore the triggering mechanisms of massive iceberg discharges and to clarify the role of the ocean in these events.